Professor Jorge Xavier da Silva - Latuf, Marcelo de Oliveira; Pisani, Rodrigo José; Bando, Daniel Hideki; Azevedo, Sandra de Castro de (Espaço Aberto, 2021)
Entrevista publicada na Revista Brasileira de Geografia, v. 62, n. 1, p. 79-94, 2017